Risk for ventricular fibrillation in peripartum cardiomyopathy with severely reduced left ventricular function—value of the wearable cardioverter/defibrillator. (5th November 2014) - Duncker, David; Haghikia, Arash; König, Thorben; Hohmann, Stephan; Gutleben, Klaus‐Jürgen; Westenfeld, Ralf; Oswald, Hanno; Klein, Helmut; Bauersachs, Johann; Hilfiker‐Kleiner, Denise; Veltmann, Christian
<x xml:space="preserve">Abstract</x> Aims The true incidence of life‐threatening ventricular tachyarrhythmic events and the risk of sudden cardiac death in the early stage of peripartum cardiomyopathy (PPCM) are still unknown. We aimed to assess the usefulness of the wearable cardioverter/defibrillator (WCD) to bridge a potential risk for life‐threatening arrhythmic events in patients with early PPCM, severely reduced left ventricular ejection fraction (LVEF) and symptoms of heart failure. Methods and results Twelve consecutively admitted women with PPCM were included in this single‐centre, prospective observational study between September 2012 and September 2013. Patients with LVEF ≤35% were considered to use the WCD for 3 months or even 6 months when considered necessary for LVEF recovery. Nine of the 12 women had a severely reduced LVEF (mean 18.3%) at the time of study enrolment; seven women received a WCD, while two patients refused to wear a WCD. During a median WCD follow‐up of 81 days (range 25–345 days), we observed a total of four events of ventricular fibrillation with appropriate and successful WCD shocks in three of the seven women receiving a WCD. No syncope or sudden arrhythmic deaths occurred in women not using the WCD during a median follow‐up of 12 months (range 5–15 months). All women showed impressive improvement of LVEF during follow‐up. Conclusion PPCM patients with severely reduced LVEF have an elevated risk for ventricular tachyarrhythmias early after diagnosis. Therefore, use of the WCD should be considered in all women with early‐stage PPCM and severely reduced LVEF during the first 6 months after initiation of heart failure therapy.